A grid integration planning approach for partitioned super-large offshore wind farms considering onshore grid accommodation capacity - Xu, Ling; Zhang, Mengyao; Zhang, Xiaohu; Zhao, Le; Ling, Jingwen; Bian, Xiaoyan (Frontiers in Energy Research, 2025)
Large-scale offshore wind energy development is crucial for energy transition. At present, there is no consideration of onshore grid accommodation capacity when integrating and planning offshore wind farm systems, which severely constrains the deployment of giga-scale projects, i.e., super-large offshore wind farms (SLOWFs). To achieve rational accommodation of wind power, we propose a transmission system planning method for partitioned SLOWFs by considering the accommodation capacity of the onshore power grid. First, based on the constraints of the onshore partition grid’s accommodation capacity, we apply the density peak clustering algorithm to partition the SLOWF. Second, a double-layer planning model is established for the transmission system of the partitioned SLOWF; here, the upper-layer model focuses on layout optimizing of the offshore converter stations based on the partitioned SLOWF, while the lower-layer model addresses the planning of DC submarine cables and onshore converter stations. The overall economic optimization of the system is achieved by iteratively solving the double-layer model. Finally, the simulations are validated using the links of a SLOWF integrated with an actual coastal grid. The results demonstrate that the proposed model and solution method significantly reduce planning costs while improving the efficiency of convergence.